Community Service for Accounting Teacher Working Forum to Enhance Skills in Creating Learning Videos and Utilising Digital Collaboration Spaces - Ani Widayati; Eka Ary Wibawa; Rizqi Ilyasa Aghni; Arif Rahman Hakim; Pradana Setialana (Universitas Lambung Mangkurat, 2024)
Teachers need to improve their skills to be able to teach effectively in the digital age. However, a situational analysis shows that accounting teachers at the MGMP SMK Kulon Progo Regency can still not utilise ICT to create video learning materials and digital collaboration spaces. As a solution to these problems, the community service team is committed to conducting community service related to training and assistance in creating video learning materials and utilising digital collaboration spaces using the participatory action research method. The Community service participants were 21 Kulon Progo Regency Vocational School Accounting (MGMP) teachers. The steps for Community service activities are 1) delivery of material on basic concepts of learning media; 2) practice of creating media; 3) material on collaborative learning; 4) practice of collaborative learning and working in accounting learning; 5) practice of designing collaborative learning material using technology; 6) independent work by the teacher for 2 weeks; 6) presentation of the results of independent work; and 7) servants reviewing practical assignments for making learning videos and utilising digital collaboration spaces. The results of Community service activities are: 1) increasing the ability of accounting teachers to make learning videos and 2) increasing the ability of accounting teachers to utilise digital collaboration spaces to support collaborative learning and working. The achievement of Community service results is supported by several factors, namely the solidity of the service team, cooperation agreements between the service team and partners, smooth communication between the service team and partners, as well as the suitability of training materials to the needs of target partners.